(untitled) (Research, Society and Development, 2020)
The aim is to map the global scientific production (national and international) referring to the theoretical framework Mathematics Teacher’s Specialized Knowledge - MTSK in the Google Scholar database between 2011 and 2019. For this purpose, we carried out a descriptive-bibliographic research of bibliometric character in the referred database. We started from a set of 799 works, of which 323 formed the corpus of analysis regarding the categories: (i) distribution of production per year, (ii) authors, (iii) languages, (iv) types of production. The results show a much larger number of works and authors (315) involved with MTSK than those previously found. Given its characteristics, we concluded, in line with previous studies, that there is a substantial increase in production, that there is a more prolific group of researchers working collaboratively and internationally, with a predominance of articles in Spanish and Portuguese, among others. As a novelty, we identified an increase in MTSK production in Brazil proportionally much greater than the global one, a consistent annual increase in the entry of new researchers, more types of publications and their relevance, among others. In the face of this scenario of increasing interest and dissemination of the MTSK framework, we point out to those who may be interested in our results and highlight the paths of new research in progress.